Petroleum Policy and Collective Rights; A comparative analysis of 2003 and 2013. Case study: The waorani - Danjiela Cvetich, Kristina (2017)
The central objective of this work is to determine the role of the State in the Ecuadorian petroleum policies of 2003 and 2013 and its effect on the Waorani Nation. Through an International Relations approach to this topic, one can explore how the international political economy has very direct impacts on specific populations, in regards to security and human rights. A study of Ecuador and its management of the natural resource of petroleum will be presented through Critical Theory ontology, epistemology and methodology.